THE ELEMENTS OF THE MOVIE â€œKALAM-KALAM LANGITâ€ AND ITS EFFECT ON VISIT INTENTION OF HALAL TOURISM DESTINATION: THE MEDIATION OF AFFECTIVE IMAGE AND COGNITIVE IMAGE - Wawan Saputra; Azis Slamet Wiyono (IAIN Surakarta, 2021)
This study seeks to determine the effect of elements in the movie â€œKalam-Kalam Langitâ€ on the visit intention of halal tourism destinations through affective and cognitive image. This study employed a quantitative approach with 100 respondents whose specific criteria of have watched the movie â€œKalam-Kalam Langitâ€. Questionnaires were distributed offline and online using Google Forms. Nonprobability sampling was used for sampling techniques. The data analysis method was multiple regression analysis and multiple testing employing SPSS version 2.3 to determine the relationship of independent and dependent variables through mediating variables. The results show that there is a positive and significant effect of elements in the movie on cognitive and affective images. The results also show that affective and cognitive images have a significant positive effect of the elements in the movie â€œKalam-Kalam Langitâ€ on the visit intention of tourist attractions in the movie. However, the results showed that the cognitive image and the affective image did not mediate the effect of the elements in the movie on the visit intention of tourism destinations.